The effect of workplace relocation on individuals’ activity travel behavior - Francois Sprumont; Francesco Viti (Journal of Transport and Land Use)
On working days, homes and workplaces can be seen as anchor locations at the heart of daily mobility patterns, as well as being central to an employee’s activity pattern. In this study, we investigate how workplace relocation affects the entire daily activity-travel chain. While past research has shown that workplace decentralization is often associated with higher car use for the commuting trip, little is known about the effect on the whole activity travel pattern. Two waves of a two-week travel diary were completed by 43 employees of the University of Luxembourg: one before and one after the relocation of their office. Using descriptive statistics as well as standard deviational ellipses (SDE) theory combined with the results of a clustering analysis showed that workers’ activity spaces (represented by the standard deviational ellipses) were significantly modified due to the relocation of a single anchor activity location, i.e., their workplace.